Genome-Wide CRISPR/Cas9 Screen Identifies New Genes Critical for Defense Against Oxidant Stress in Toxoplasma gondii - Chen, Yun; Liu, Qi; Xue, Jun-Xin; Zhang, Man-Yu; Geng, Xiao-Ling; Wang, Quan; Jiang, Wei (Frontiers in Microbiology, 2021)
Toxoplasma gondii is one of the most widespread apicomplexans and can cause serious infections in humans and animals. Its antioxidant system plays an important role in defending against oxidant stress imposed by the host. Some genes encoding the antioxidant enzymes of T. gondii have been identified; however, critical genes that function in response to reactive oxygen species (ROS) stress are still poorly understood. Here, we performed genome-wide CRISPR/Cas9 loss-of-function screening in the T. gondii RH strain to identify potential genes contributing to the ROS stress response. Under hydrogen peroxide treatment, 30 single guide RNAs targeting high-confidence genes were identified, including some known important antioxidant genes such as catalase and peroxiredoxin PRX3. In addition, several previously uncharacterized genes were identified, among which five hypothetical protein-coding genes (namely, HP1–HP5) were selected for further functional characterization. Targeted deletion of HP1 in T. gondii RH led to significant sensitivity to H2O2, suggesting that HP1 is critical for oxidative stress management. Furthermore, loss of HP1 led to decreased antioxidant capacity, invasion efficiency, and proliferation in vitro. In vivo results also revealed that the survival time of mice infected with the HP1-KO strain was significantly prolonged relative to that of mice infected with the wild-type strain. Altogether, these findings demonstrate that the CRISPR/Cas9 system can be used to identify potential genes critical for oxidative stress management. Furthermore, HP1 may confer protection against oxidative damage and contributes to T. gondii virulence in mice.